Simulation of WCDMA radio over fiber technology - Mohd. Razali, Siti Harliza (2007)
The demand for broadband services has driven research on millimetre wave frequency band communications for wireless access network due to its spectrum availability, and compact size of radio frequency devices. However, the mm-wave signals suffer from severe loss along the transmission as well as atmospheric attenuation. In other words, upcoming wireless networks will use a combination of airinterface methods in different channels and in different cells that can be changed dynamically to meet variations in traffic conditions. One of the solution to overcome these problem is by using low-attenuation, electromagnetic interference-free optical fiber. Radio over Fiber (RoF) is integration of optical fiber for radio signal transmission within network infrastructures that is considered to be cost-effective, practical and relatively flexible system configuration for long-haul transport of millimetric frequency band wireless signals. This project is about to simulate WCDMA Radio Over Fiber using Matlab Simulink. By doing so, the efficiency can be measured by the performance of BER (Bit Error Rate). The finding of this project is the WCDMA RoF is suite with 3G and 4G application along with increasing users every year whole the world. The conclusion is the simulation of WCDMA RoF was success developed throughout objective.